Analysis and calibration of system errors in steerable parametric loudspeakers - Gan, Woon-Seng (2013)
By adjusting a set of delay amounts and amplitudes of the ultrasonic transducer (primary source) array in parametric loudspeakers, the directional sound beam can be steered within a range of predefined angles. This beamsteering characteristic of parametric loudspeakers has been proposed in theory and validated by measurements. In particular, the locations of the mainlobe and grating lobes can be predicted within a certain degree of accuracy in theory. However, errors incur in different stages of implementation. Thus, mismatches are observed between theoretical and measured beampatterns. In this paper, four types of system errors are analyzed for the primary-frequency waves and the difference-frequency waves based on the phased array theory and the product directivity principle, respectively. The degraded beampatterns which are caused by system errors are analyzed and calibrated by using a combined optimization approach of Monte Carlo method and nonlinear least squares method. Experimental results are presented to show the advantage of the proposed calibration method that leads to significant reduction of mismatch between theoretical and measured beampatterns at both the primary frequency and the difference frequency.